Arqueologia da ausência – um processo privado de elaboração da perda em audiovisuais de familiares de desaparecidos na ditadura Argentina ( 1976-1983) - Oliveira, Euller Gontijo de (2013)
This work aims to study the role of the cinema thinking in the reconfiguration of memory and in the constitution of identities, through two films directed by relatives of missing the last Argentine military regime. We found the films an excellent source of study to think building these memories in film. In this sense, the main axis of reflection is how these relatives, today filmmakers, come thinking your memories and their identities from their audiovisual production? What place the images in this building? And to what extent the images contribute to the remodeling of the memory and, therefore, identities, since we assume that memory and identity do not dissociate. From this perspective presented by Joël Candau (2011) analyze the two documentaries, starting from the design of the memory can both consolidate as weakening the sense of identity. In this sense, a focus of this work is to think like documentaries Argentine military dictatorship come after linking and updating the past in a struggle against forgetting.